Analisis Pendapatan Nelayan Pemilik Bagang Perahu: Studi Kasus Di Kecamatan Bontoharu Kabupaten Kepulauan Selayar - Nurul Nadya; Wa Ode Rayyani (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the income of fishermen who own bagang boats in Bontoharu District, Selayar Islands Regency. Qualitative methods are used to deeply understand the factors that influence fishermen's income, including social, economic, and environmental aspects. Data were collected through in-depth interviews with fishermen, direct observation, and analysis of related documents. The results of the study indicate that fishermen's income is influenced by various factors, such as the type of fish caught, fishing season, and access to markets. In addition, challenges faced by fishermen, such as climate change and government policies, also contribute to income fluctuations. These findings are expected to provide insight for policy makers in formulating better strategies to improve the welfare of fishermen in the area.